Analisis kebutuhan pegawai di Balai Taman Nasional Alas Purwo - vera tisnawati; Rinekso Soekmadi; Agus Priyono Kartono (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Every year, starting from 2015-2019, the effectiveness of Alas Purwo National Park (APNP) management is evaluated, by using the Management Effectiveness Tracking Tool (METT). This assessment system requires valid data and information for objective results. One of the data and information needed is the result of staffs requirement analysis. The objective of this research is to analyze the need of staffs of APNP Office in 2017-2019. The study began in May 2017 until January 2018 and took place at APNP Office in Banyuwangi and in Staffing, Organization and Governance Office of the Secretariat of the Directorate General of Natural Resources Conservation and Ecosystem in Bogor. The data collected by observation, discussion and document study result. The analysis begins by calculating the staffs inventory, then calculating the required staffs based on the workload and ending by calculating the adequacy of the staffs. The results show that Overall, the number of staffs at BTNAP in 2017-2019 has exceeded the number of staffs required, but in function (administrative and technical personnel) there is still inequality, especially in the position of data analysts, data processors, and revenue treasurer.